Human genome mutation and rearrangement studies – the way to investigate monogenic and complex disease pathogenesis - Livshits, L.A.; Kravchenko, S.A.; Nechyporenko, M.V.; Pampukha, V.M.; Hryshchenko, N.V.; Livshyts, G.B.; Soloviov, O.O.; Tatarskyy, P.F.; Fesai, O.A.; Chernushyn, S.Yu.; Kucherenko, A.M.; Gulkovskyy, R.V. (Вiopolymers and Cell, 2013)
The summarized results of 25-year studies of department of human genomics of IMBG NASU are presented. The investigations were focused on identification of molecular genetic nature of human genome coding and non-coding region mutations (genetic polymorphisms) and rearrangements, their spectrum, and origin in Ukrainian population. The role of genome heterogeneity in some severe monogenic and complex disorder pathogenesis has been shown. The data concerning correlation between certain determinator gene mutations and phenotypical manifestation of most common in Ukraine monogenic diseases have been demonstrated. Moreover, the role of modifying genes in specific clinical phenotype variations has been shown. Origin of particular mutant alleles and main mechanisms of their frequency maintenance in Ukrainian population have been investigated. The data about association of some polymorphic variants with infertility, cardiovascular diseases (ischemic stroke) as well as mass infectious diseases (hepatitis C, AIDS) outcome and standard therapy efficiency have been presented. The first results and prospects for candidate genes of neurodegenerative disorders and intellectual disability search using whole genome CNVs screening are shown. Підсумоввано результати 25-літніх досліджень співробітників відділу геноміки людини ІМБіГ НАН України, спрямованих на з’ясування молекулярно-генетичної природи, спектра і походження в популяції України мутацій (генетичних поліморфізмів) та реорганізацій кодуючих і некодуючих ділянок геному людини. Встановлено роль гетерогенності геному в патогенезі тяжких моногенних і мультифакторних патологій. Отримано дані щодо кореляції певних мутацій генів-детермінаторів з фенотиповими проявами моногенних захворювань, а також обговорено роль генів-модифікаторів у варіаціях клінічного фенотипу. Досліджено походження окремих мутантних алелів та знайдено основні закономірності процесів підтримання їхньої частоти в популяції України. Представлено дані стосовно асоціації деяких поліморфних варіантів з безпліддям, серцево-судинними захворюваннями (ішемічний інсульт), а також з масовими інфекційними хворобами (гепатит С, СНІД) та показано ефективність стандартної терапії. Продемонстровано перші результати і перспективи нової стратегії пошуку генів – маркерів нейродегенеративних захворювань та інтелектуальної недієздатності за рахунок повногеномного скринінгу геномних реорганізацій типу CNV. Обобщены результаты 25-летних исследований сотрудников отдела геномики человека ИМБиГ НАН Украины, направленных на выяснение молекулярно-генетической природы, спектра и происхождения в популяции Украины мутаций (генетических полиморфизмов) и реорганизаций в кодирующих и некодирующих участках генома человека. Установлена роль гетерогенности генома в патогенезе тяжелых моногенных и мультифакторных патологий. Получены данные о корреляции определенных мутаций генов-детерминаторов с фенотипическими проявлениями моногенных заболеваний, а также обсуждена роль генов-модификаторов в вариациях клинического фенотипа. Исследовано происхождение отдельных мутантных аллелей и установлены основные закономерности процессов поддержания их частоты в популяции Украины. Представлены данные об ассоциации некоторых полиморфных вариантов с бесплодием, сердечно-сосудистыми заболеваниями (ишемический инсульт), а также с массовыми инфекционными болезнями (гепатит С, СПИД) и показана эффективность стандартной терапии. Продемонстрированы первые результаты и перспективы новой стратегии поиска генов – маркеров нейродегенеративных заболеваний и интеллектуальной недееспособности за счет полногеномного скрининга геномных реорганизаций типа CNV.